Ruski miesiac z hakiem - Pomianowski, Jerzy, 1921- (Wroclaw : Wydawn. Dolnoslaskie, 1997)
Various political essays on the relations between Poland and the new Russia.
Keywords: Public opinion -- Poland; Poland -- Relations -- Russia (Federation); Russia (Federation) -- Relations -- Poland; Russia (Federation) -- Foreign public opinion, Polish